Pengaruh Likuiditas dan Profitabilitas Terhadap Kinerja Keuangan Pada Perusahaan Makanan dan Minuman yang Terdaftar di BEI Periode 2020-2022 - Rahayu, Aprilia Sri (Jaanur Elbarik Indonesia, 2025)
This study aims to analyze the effect of liquidity and profitability on the financial performance of food and beverage companies listed on the Indonesia Stock Exchange (IDX) during 2020–2022. Liquidity is measured using the Quick Ratio (QR), profitability using the Gross Profit Margin (GPM), and financial performance is proxied by Return on Equity (ROE). This research employs a quantitative method using secondary data from financial statements, with a purposive sampling technique. Data analysis was conducted using SPSS version 27, and the results indicate that QR has a significant effect on ROE (t = 2.033; sig = 0.045), while GPM also has a significant effect on ROE (t = 4.128; sig = 0.000). The Adjusted R Square value of 0.244 suggests that 24.4% of ROE variation is explained by QR and GPM, while the remaining 75.6% is influenced by other factors outside the model. These findings highlight the importance of effective liquidity and profitability management in enhancing financial performance amid intense industry competition.